The qualitative variation of Katingan cattle - Utomo, Bambang Ngaji; Noor, R.R.; Sumantri, C; Supriatna, I; Gunardi, E.D; Tiesnamurti, B (Indonesian Animal Sciences Society, 2012)
The characterization is main activities in order to identify important trait of Katingan cattle. Information of its phenotypic characteristic is not available yet. The aim of the study is to describe the qualitative characteristic of Katingan cattle. Three location of the study were sub-district of Tewah Sanggalang Garing (Pendahara Village), sub-district of Pulau Malan (Buntut Bali Village), and sub-district of Katingan Tengah (Tumbang Lahang Village). The samples of Katingan cattle were taken as many as possible based on the field conditions to observe pattern of colour, growth of horn and gibbosity appear among two horns. General characteristic of Katingan cattle was various in colours of coat, having horns, humped and dewlop. The main characteristics were expressed at female of Katingan cattle. There were six variations of horn shape at female, however the growth of arching forwards was dominant (78.4%). Horn shape of male was generally grown upside (98.3%). Gibbosity was founded among horn only at female cattle (92.6%). There were 9 combinations of coat colour of female Katingan Cattle, those were brown reddish (27%), brown whitish (14.1%), brown like colour of Bali cattle (13.8%), black (12.5%), brown dull (9.6%), brown sorrel (9.3%), blackish (7.1%), white brownish (5.5%) and white grayish (4.5%). Male of Katingan cattle had eight colour combinations, those were brown whitish (14.8%), brown whitish and reddish (14.8%), brown reddish (13.1%), blackish (12.3%), brown whiteish with black withers (10.7%), brown sorrel (9.8%) and brown sorrel with black withers (7.8%). Based on qualitative analysis, the Katingan cattle had variations in coat of colour, growth of horn and the gibbosity. The variation of coat colour had potentially selection related to the value of cultural. Key Words: Katingan Cattle, Qualitative, Coat Colour, Horn, Gibbosity